Eradication of Krebs-2 primary ascites via a single-injection regimen of cyclophosphamide and double-stranded DNA - E. A. Potter; E. V. Dolgova; A. M. Minkevich; V. P. Nikolin; N. A. Popova; Ya. R. Efremov; S. I. Baiborodin; V. A. Rogachev; A. S. Proskurina; O. S. Taranov; E. I. Vereschagin; A. A. Ostanin; et al. (Вавиловский журнал генетики и селекции)
Previously, we reported on the development of a therapeutic regimen allowing eradication of primary murine Krebs-2 ascites transplants. This protocol involved multiple injections of dsDNA preparations administered during the NER and HR phases of repair of interstrand DNA cross-links induced by prior cyclophosphamide treatments. Mice treated under this protocol frequently developed secondary ascites, which indicated that some tumor-inducing cancer stem cells could survive the treatment and caused relapse. Further, we observed that animals receiving multiple dsDNA injections developed pronounced systemic inflammatory response. This prompted us to develop a more straightforward treatment regimen based on the synergistic activity of cyclophosphamide and dsDNA preparations, which would allow complete eradication of established primary Krebs-2 ascites and also be less toxic for the treated animals. This protocol relies on a precisely timed single injection of dsDNA during the NER/HR transition period of each repair cycle. Under this protocol, 8-day remission of Krebs-2 engrafted mice was achieved, which was similar to the results of the multiple-injection treatment schedule. We observed an increase in the average life span of Krebs-2- transplanted mice on a single-injection regimen, which was consistent with reduced toxicity of such treatment.